Modern research trends in research and measurement studies in public relations: A second-level analytical study on a sample of scientific, Arab, and foreign journals in the field of public relations and communication - Hasaballah, Al-Nourani Muhammad Al-Hassan (International Journal of Innovative Research and Scientific Studies, 2025)
The study aimed to identify the modern research trends in the field of public relations research and the measurement in scientific journals published in Arabic and English literature. The descriptive analytical approach was used, employing the second-level analysis method that is based on reusing data resulting from public relations research that addressed the topic of research and measurement as a process in this field. The analysis provides a valuable source of field data and office information that enables researchers to develop the practice of public relations research and measurement in various institutions. The study concluded with a number of results, the most important of which is that research and measurement in public relations are important topics for both academics and practitioners alike, and still require more effort. In addition, the study showed that there is diversity in public relations measurement studies, without efforts to develop scientific measures that contribute to the advancement of this field.